17‐Hydroxyprogesterone caproate in triplet pregnancy: an individual patient data meta‐analysis. (10th December 2015) - Combs, CA; Schuit, E; Caritis, SN; Lim, AC; Garite, TJ; Maurel, K; Rouse, D; Thom, E; Tita, AT; Mol, BWJ; ,
Abstract : Background: Preterm birth complicates almost all triplet pregnancies and no preventive strategy has proven effective. Objective: To determine, using individual patient data (IPD) meta‐analysis, whether the outcome of triplet pregnancy is affected by prophylactic administration of 17‐hydroxyprogesterone caproate (17OHPc). Search strategy: We searched literature databases, trial registries and references in published articles. Selection criteria: Randomised controlled trials (RCTs) of progestogens versus control that included women with triplet pregnancies. Data collection and analysis: Investigators from identified RCTs collaborated on the protocol and contributed their IPD. The primary outcome was a composite measure of adverse perinatal outcome. The secondary outcome was the rate of birth before 32 weeks of gestation. Other pre‐specified outcomes included randomisation‐to‐delivery interval and rates of birth at <24, <28 and <34 weeks of gestation. Main results: Three RCTs of 17OHPc versus placebo included 232 mothers with triplet pregnancies and their 696 offspring. Risk‐of‐bias scores and between‐study heterogeneity were low. Baseline characteristics were comparable between 17OHPc and placebo groups. The rate of the composite adverse perinatal outcome was similar among those treated with 17OHPc and those treated with placebo (34 and 35%, respectively; risk ratio [RR] 0.98, 95% confidence interval [95% CI] 0.79–1.2). The rate of birth at <32 weeks was also similar in the two groups (35 and 38%, respectively; RR 0.92, 95% CI 0.55–1.56). There were no significant between‐group differences in perinatal mortality rate, randomisation‐to‐delivery interval, or other specified outcomes. Conclusion: Prophylactic 17OHPc given to mothers with triplet pregnancies had no significant impact on perinatal outcome or pregnancy duration. Tweetable abstract: 17‐Hydroxyprogesterone caproate had no significant impact on the outcome or duration of triplet pregnancy. Tweetable abstract: 17‐Hydroxyprogesterone caproate had no significant impact on the outcome or duration of triplet pregnancy.